2007
DOI: 10.1055/s-2007-967082
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Deoxyribonuclease Activity in Monoglandular and Polyglandular Autoimmunity

Abstract: These findings indicate the potential relevance of DNase activity in patients with monoglandular and polyglandular autoimmunity and their clinically healthy relatives. The impaired DNase activity might reduce removal of circulating self- or pathogen-derived DNA thereby favoring autoimmune mechanisms by Toll-like receptor 9 co-activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
8
1
Order By: Relevance
“…These findings allow us to conclude that DNASE1 is able to tolerate the generation of non-synonymous SNPs, and furthermore that the amino acid substitutions resulting from the SNPs easily create alterations in the levels of enzyme activity in comparison with DNASE1L3. It has been reported that, in comparison with healthy subjects, levels of serum DNase I activity are reduced in patients with SLE [36][37][38][39]. Recently, Rekvig and colleagues have demonstrated that in lupus nephritis, which is the most serious complication of SLE, downregulation of renal DNase I results in reduced chromatin fragmentation and deposition of extracellular chromatin-IgG complexes in the glomerular basement membranes in subjects that produce IgG antibodies against chromatin [8,40].…”
Section: Discussionmentioning
confidence: 99%
“…These findings allow us to conclude that DNASE1 is able to tolerate the generation of non-synonymous SNPs, and furthermore that the amino acid substitutions resulting from the SNPs easily create alterations in the levels of enzyme activity in comparison with DNASE1L3. It has been reported that, in comparison with healthy subjects, levels of serum DNase I activity are reduced in patients with SLE [36][37][38][39]. Recently, Rekvig and colleagues have demonstrated that in lupus nephritis, which is the most serious complication of SLE, downregulation of renal DNase I results in reduced chromatin fragmentation and deposition of extracellular chromatin-IgG complexes in the glomerular basement membranes in subjects that produce IgG antibodies against chromatin [8,40].…”
Section: Discussionmentioning
confidence: 99%
“…It catalyzes DNA hydrolysis by cleaving double-stranded DNA. The activity of this enzyme was lowered in patients with PAS compared to healthy subjects (21,22). Such a deficiency in DNase 1 may result in reduced or delayed removal of DNA from nuclear antigens and, thereby, may promote disease susceptibility to autoimmune disorders.…”
Section: Innate Immunity and The Enzyme Deoxyribonucleasementioning
confidence: 94%
“…Decreased serum DNase activity with elevated levels of circulating DNA and resulting activation of the TLR9 immunostimulating pathway can also trigger organ-specific autoimmune disease. Most of the natural insulin Abs are polyreactive and bind in addition to insulin one or more antigens including thyroglobulin (Tg), IgG and DNA (21). Complexes containing DNA between polyreactive natural Abs, i.e.…”
Section: Innate Immunity and The Enzyme Deoxyribonucleasementioning
confidence: 99%
“…Blood samples were drawn in the morning and serum samples were immediately frozen at À20 C. Serum DNase activity was determined with a standardized, validated, and reproducible enzyme-linked-immunosorbent assay, as described earlier [20]. In brief, DNase substrate was used as a solid phase and the serum DNase degraded the DNase substrate.…”
Section: Measurement Of Dnase Activitymentioning
confidence: 99%
“…Recently, we have shown impaired DNase activity in patients with endocrine autoimmunity [20]. But so far, no molecular studies were performed in the DNASE1 gene in these patients.…”
Section: Introductionmentioning
confidence: 99%